Golden ratio - Pukhlakova, Tamara; Radzievska, Elena (My University, 2014)
In modern science, interest in the Golden Section has increased with new vigor. Golden Section proved a source of new and fruitful ideas in mathematics, theoretical physics and crystallography, economics, biology, botany, computer science, coding theory and cryptography. I believe that the study of the golden ratio opens wide horizons in modern science.
Keywords: golden ratio; modern science; золотий перетин; сучасна наука; золотое сечение; современная наука